2018
DOI: 10.1038/s41598-017-18543-z
|View full text |Cite
|
Sign up to set email alerts
|

Innate IFN-γ ameliorates experimental autoimmune encephalomyelitis and promotes myeloid expansion and PDL-1 expression

Abstract: The innate immune system plays a central role in the immune-mediated pathology of multiple sclerosis, and is a therapeutic target for progressive disease. Recently, it has been demonstrated that MIS416, a novel immunomodulatory microparticle that activates NOD-2 and TLR-9-signaling, has disease-modifying activity in multiple sclerosis models. This activity is dependent on innate IFN-γ; however, the precise immune regulatory mechanisms amplified by MIS416 have not previously been determined. Using the experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 31 publications
(47 reference statements)
3
34
2
Order By: Relevance
“…These were upregulated in CNS by intrathecal MIS416. Intrathecal and intravenous MIS416 both induced PDL-1+ myeloid populations, shown to be IFNγ-dependent in the case of peripheral suppression, where PDL-1+ monocytes also infiltrated the CNS [34]. PD1 inhibitory signaling may be considered as a possible mechanism for intra-CNS EAE suppression, although in the present study, PDL-1 was expressed by both the neutrophils and monocytes that were recruited by MIS416, so did not correlate with suppressive function.…”
Section: Discussioncontrasting
confidence: 65%
See 4 more Smart Citations
“…These were upregulated in CNS by intrathecal MIS416. Intrathecal and intravenous MIS416 both induced PDL-1+ myeloid populations, shown to be IFNγ-dependent in the case of peripheral suppression, where PDL-1+ monocytes also infiltrated the CNS [34]. PD1 inhibitory signaling may be considered as a possible mechanism for intra-CNS EAE suppression, although in the present study, PDL-1 was expressed by both the neutrophils and monocytes that were recruited by MIS416, so did not correlate with suppressive function.…”
Section: Discussioncontrasting
confidence: 65%
“…PD1 inhibitory signaling may be considered as a possible mechanism for intra-CNS EAE suppression, although in the present study, PDL-1 was expressed by both the neutrophils and monocytes that were recruited by MIS416, so did not correlate with suppressive function. Suppression of EAE by iv-administered MIS416 was dependent on innate IFNγ [34], whereas we show dependence on Type I IFN. In another study we showed that IFNγ could substitute for Type I IFN signaling [2], and it cannot be excluded that an analogous functional overlap contributed in the myeloid suppression of CNS inflammation that we describe here.…”
Section: Discussioncontrasting
confidence: 51%
See 3 more Smart Citations